2009
DOI: 10.1158/0008-5472.can-08-4400
|View full text |Cite
|
Sign up to set email alerts
|

ARTEMIS Nuclease Facilitates Apoptotic Chromatin Cleavage

Abstract: One hallmark of apoptosis is DNA degradation that first appears as high molecular weight fragments followed by extensive internucleosomal fragmentation. During apoptosis, the DNA-dependent protein kinase (DNA-PK) is activated. DNA-PK is involved in the repair of DNA double-strand breaks (DSB) and its catalytic subunit is associated with the nuclease ARTEMIS. Here, we report that, on initiation of apoptosis in human cells by agents causing DNA DSB or by staurosporine or other agents, ARTEMIS binds to apoptotic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…C-NHEJ may account for translocation events in some specific situations such as during the recovery from early apoptotic DNA fragmentation [230][231][232], or in the pathogenesis of acute leukemias secondary to cancer treatments based on Topoisomerase-II (TopoII) inhibitors that frequently feature translocations involving the mixed-lineage leukemia (MLL) gene [233,234]. The role of C-NHEJ in chromosomal rearrangements has been more clearly established in the special case of one-ended DSB repair following replication fork collapse [235][236][237][238], but a recent study also suggests a significant role for A-EJ in the repair of one-ended DSBs following hydroxyurea replication fork arrest [83].…”
Section: End-joining Processes In Chromosomal Rearrangementsmentioning
confidence: 99%
“…C-NHEJ may account for translocation events in some specific situations such as during the recovery from early apoptotic DNA fragmentation [230][231][232], or in the pathogenesis of acute leukemias secondary to cancer treatments based on Topoisomerase-II (TopoII) inhibitors that frequently feature translocations involving the mixed-lineage leukemia (MLL) gene [233,234]. The role of C-NHEJ in chromosomal rearrangements has been more clearly established in the special case of one-ended DSB repair following replication fork collapse [235][236][237][238], but a recent study also suggests a significant role for A-EJ in the repair of one-ended DSBs following hydroxyurea replication fork arrest [83].…”
Section: End-joining Processes In Chromosomal Rearrangementsmentioning
confidence: 99%
“…[24] The Comet assay measures DNA damage as the extent of single and double-strand breaks [16] which might be due to the activation of nuclease. [25] The mean percentage of the comet showed a dose-time-dependent increase after treatment with cadmium chloride when compared to control, thus it might be concluded that even lower dose of cadmium chloride after long-term toxicity can induce morphological changes in nuclei and cytoplasm as well as nuclear breakage of the MSCs which can be considered as a risk factor that affects the bone health in industrial or other contaminated areas.…”
Section: Discussionmentioning
confidence: 96%
“…The cells were plated in appropriate culture dish and allowed to attach for 24 h, then in the presence of the control group, the cells were exposed to 5,15,25,35, and 45 µM of cadmium chloride (Merck Company, Germany). Number of the plated cells and time of exposure were calculated according to the nature of the test and dimension of the culture dish which is mention where ever it is necessary.…”
Section: Exposure To Cadmium Chloridementioning
confidence: 99%
See 1 more Smart Citation
“…Among the targeted genes and in using our approach we have always obtained at least one vector able to impose long-term shut down greater than 80% as compared with control cells (as evidenced by realtime RT-PCR). Using this technology, more than 160 human genes in different human cell models such as HeLa (Ame et al, 2009, Amine et al, 2009, Aressy et al, 2008, Betous et al, 2009, Biard, 2007, Biard et al, 2005, Biard & Angulo, 2007, Boehler et al, 2011, Bouley et al, 2010, Britton et al, 2009a, Despras et al, 2007, Godon et al, 2008, Le May et al, 2010b, Ousset et al, 2010, Pennarun et al, 2008, Pennarun et al, 2010, Wu et al, 2007, U2OS (Betous et al, 2009) and MRC5-V1 (Bouquet et al, 2011, Britton et al, 2009b, Schmutz et al, 2010 cells have been silenced. Our approach has also been successfully tested in other human tumorderived cell lines, such as RKO (Biard & Angulo, 2007), HCT-116 (Aressy et al, 2008), Caco2 (Coant et al, 2010), SH-SY5Y cells (Schulte et al, 2008), MCF7, MDA-MB 231, K562, UT7 (papers in preparation), and even in mouse NIH-3T3 cells (Meulle et al, 2008).…”
Section: Long Term Silenced Human Cellsmentioning
confidence: 99%